URGENSI PERLINDUNGAN HAK ANAK DALAM DINAMIKA KELUARGA: PERSPEKTIF HUKUM INDONESIA DAN HUKUM INTERNASIONAL - Khofifah, Nurul; Budoyo, Sapto; Lathifah, Nadea (Universitas Stikubank, 2026)
ABSTRACT Family dynamics such as prolonged conflicts, the existence of domestic violence, divorce, and the absence of one parent figure in the family, have become international issues. Children are often victims of parental problems. Parents often vent their emotions to their children in the form of verbal and non-verbal violence. There are still many parents who think that educating children with violence is a way to discipline children. In this study, the approach method applied is a normative juridical approach by examining data obtained from books, journals, the internet, laws and regulations, or scientific papers related to this writing. Based on the results of the study, we know that by 2025, Indonesia will have recorded 2,416 cases of violence committed by parents, based on data that occurred during the official SIMFONI-PPA period. Children have the right to be able to live a prosperous life and be guaranteed their growth and development in the future. But in practice, parents are still very irresponsible for it. In overcoming these problems, the Indonesian government and the international community have made efforts with regulations and institutions related to the protection of children's rights. Therefore, it can be concluded that this study emphasizes the importance of improving the protection of children's rights in family dynamics based on the framework of Indonesian and International Law. Keywords: family dynamics, protection of children's rights, challenges and obstacles.